Deaf patient perspectives of healthcare provider cultural competency: Strategies for improvement across affective, cognitive, and behavioral dimensions - Hall, Sarah M.; Ballard, Michael; Smith, R. Parker; Mitchell, Hannah; Packard, Sophia; Major, Sarah; Kennerley, Michael; Walker, Brian (SSM. Qualitative research in health, 2025)
Deaf patients frequently encounter cultural and communication barriers in clinical settings, contributing to diminished trust, delayed care, and adverse health outcomes. This study explores healthcare provider cultural competency through the lived experiences of Deaf patients to identify challenges and strategies for improvement. Cultural competency was examined across affective, cognitive, and behavioral dimensions. Focus groups and individual interviews were conducted with 37 signing Deaf individuals in the United States. Sessions were co-facilitated by Deaf and hearing researchers, supported by Certified Deaf Interpreters and nationally certified hearing interpreters. Transcribed English interpretations were verified by a third-party interpreting agency. Data were analyzed in Nvivo 12 using both inductive and deductive coding. Participants reported healthcare providers frequently lacked cultural competency. Affective themes included frustration, fear, bias, and lack of motivation. Cognitive findings revealed limited provider understanding of Deaf identity, culture, communication needs, access barriers, and patient rights. In the behavioral dimension, providers often failed to ensure information access, communicate directly with patients, maintain visual attention, or use appropriate body language, facial expressions, volume, and pacing. Turn-taking and comprehension checks were often absent. These cross-cultural communication practices adversely impacted patients’ emotional, psychological, and physical well-being. This study offers actionable recommendations for medical institutions, healthcare organizations, providers, and Deaf patients. Proposed reforms include Deaf cultural competency training using inclusive disability models, recruitment of ASL-fluent personnel, reliable interpreter access, extended consultation lengths, provider self-reflection, patient feedback, and involvement of the Deaf community. These strategies aim to promote equity and improve care outcomes for Deaf patients. •Provider cultural competency impacts Deaf patients' physical and mental health.•Bias and audism shape access to health information and quality of care.•Gaps in provider knowledge of Deaf culture fuels mistrust.•Direct communication with eye contact and turn-taking builds trust.•Inclusive disability models and Deaf community input is vital to training efforts.